PERAN PROGRAM LITERASI PAGI DALAM MENINGKATKAN MINAT DAN KEMAHIRAN MEMBACA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Padil Asrodi; Elfia Sukma; Inggria Kharisma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Morning literacy programs have become one of the strategies widely implemented in elementary schools to improve students’ reading interest and reading proficiency. This study aims to systematically analyze empirical evidence regarding the effectiveness of morning literacy programs in enhancing elementary school students’ reading interest and reading skills. The method used in this study is a Systematic Literature Review (SLR) by searching scientific articles through databases such as Google Scholar and ERIC. The inclusion criteria for the articles were: (1) publications within the last five years, (2) studies focusing on morning literacy programs in elementary schools, and (3) studies presenting empirical data on the effects of the program on reading interest and reading proficiency. The results of the analysis indicate that morning literacy programs consistently have a positive impact on students’ reading interest and reading proficiency. Factors such as the selection of engaging reading materials, teacher support, and the variety of literacy activities contribute significantly to the effectiveness of the program. However, several studies also highlighted challenges in program implementation, including limited time allocation and inadequate resources. This study concludes that morning literacy programs are a promising intervention to improve literacy skills among elementary school students. The implication of this study is the importance of developing structured and sustainable morning literacy programs supported by adequate resources. Morning Literacy Program, Reading Interest, Reading Proficiency, Elementary School, Systematic Literature Review.